Corneal neuropathic pain in irritable bowel syndrome: clinical findings and in vivo corneal confocal microscopy - AKKAYA TURHAN, SEMRA (SPRINGER, 2021)
Purpose Ocular discomfort is a common symptom in central sensitization syndromes. The aim of this study was to evaluate ocular surface discomfort and related corneal changes in patients with irritable bowel syndrome. Methods Twenty-nine patients with IBS (20 female, 9 male, mean age: 45.3 +/- 10.1 years) and 37 healthy control subjects (25 female, 12 male, mean age: 44.95 +/- 9.76 years) were included. A detailed ophthalmological examination was performed to all participants including tear break-up time (TBUT) and Schirmer test I with anesthetic (SIT). Ocular discomfort was evaluated using the ocular surface disease index (OSDI) questionnaire and corneal sensation was evaluated with Cochet-Bonnet esthesiometer. Corneal subbasal nerve plexus was evaluated with in vivo corneal confocal microscopy (IVCM). Results There was no significant difference between the groups for age, gender distribution, and visual acuity. OSDI scores were significantly higher (p = 0.008) and TBUT was significantly reduced in patients with IBS compared to controls (p = 0.001 for right eye, p = 0.014 for left eye). However, there was no significant difference in corneal touch sensation and SIT results between the groups. IVCM revealed that corneal nerve fiber density, corneal nerve branch density, and corneal nerve fiber length were significantly reduced in patients with IBS (p < 0.001, p < 0.001, and p = 0.023, respectively). Conclusion Patients with IBS have increased dry eye-associated ocular surface complaints and nerve fiber loss in corneal subbasal nerve plexus. IBS should be remembered in the differential diagnosis, when there is discordance between the level of ocular surface discomfort and dry eye disease associated corneal findings.
Keywords: Confocal microscopy; Cornea; Dry eye; In vivo confocal microscopy; DRY EYE; OCULAR PAIN; PATHOPHYSIOLOGY; SENSITIVITY; DIAGNOSIS; SYMPTOMS